Evaluation of the Muara Satu Community Health Center in Lhokseumawe City's outpatient services' quality utilizing the importance-performance analysis approach and possible increase in customer value - Meilinda Dhika Putri; Bakhtiar Bakhtiar; Amri (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
A dynamic state of people, processes, environments, goods, and services that either meet or beyond expectations is known as service quality. It is vital to improve services to compete and provide higher-quality services at the Muara Satu Community Health Center through initiatives to enhance human resources and ongoing performance improvement. The Muara Satu Community Health Center has received major accreditation for its services; however, as of yet, no reassessment has been conducted. The management of Puskesmas wishes to refine the accreditation to become plenary so that patient satisfaction can serve as a gauge of the success of the center's health services provided to the community. This study aims to evaluate the degree of agreement between patient interests and satisfaction and the Muara Satu Community Health Center's service quality performance. Additionally, it seeks to identify the attributes that should be given priority for service improvement through the application of the Potential Gain in Customer Value (PGCV) method. Patients' complaints regarding services, such as uncomfortable waiting rooms and a lack of information about the ailments they were suffering from, posed a challenge for this study. Five categories were created based on 17 characteristics of the patient requests made at the health center and were given to 58 pre-selected samples. This category includes Assurance, Empathy, Tangible, Reliability, and Responsive. The Muara Satu Health Center is required to implement seven priority orders for quality improvement based on the IPA and PGCV methods, based on data processing findings. These orders include requiring the Community Health Center staff to inform patients before providing services, having a comfortable waiting area, and having officers act quickly and appropriately when necessary. Facilities in Puskesmas are fully equipped. The types of ailments, their treatments, and how to take medication are all thoroughly explained by the doctor. Furthermore, physicians allot enough time for patient examinations